The Position of Husband and Wife in the Indonesian Marriage Law: A Mubadalah Perspective - Marhamah Al-Eser; Suratno Suratno; Arif Fikri (Brajamusti Publication, 2024)
This article is about the position of husband and wife regulated in Article 31 of the Indonesian Marriage Law (UUP). The provisions of the position of husband and wife are allegedly gendered and contradictory, because they place husbands and wives not on equal footing, Article 31 when read textually has implications for the subordination of women. The purpose of this article is to analyse the provisions of the position of husband and wife in the Indonesian Marriage Law from the perspective of Mubadalah. Mubadalah theory is used to analyse the equality of husband and wife in the household. The method used is qualitative, the type of this article is librabry research (library research), a normative approach with a focus on analysing Article 31, data sources are obtained from literature related to mubadalah. The results show that Article 31 of the UUP places the position of husband and wife differently, the husband as the head of the household while the wife is a housewife, this text can be gendered and seems masculine. In the perspective of mubadalah, Article 31 of the UUP is not in line with the values of justice and equality. Article 31 of the UUP needs a jucial review for the realisation of a maslahah family based on the principle of equality between husband and wife in the household.